Czas do 19.00!
Wykonaj działania i zredaguj wyrazy:
3(2x-4)-5(4x+7) =?
(2x-6) (3x+5)+4x-9 =?
(2a-3) (5-4a)-6a (2a+4) =?

Oblicz wartość wyrażenia:
a) 3x-4y+7 , x = -2 , y = -5
b) 6x-8y+12+x² , x= -2 , y= 1½
c) 12a-16b+8 , a= ¾ , b=5/8 (pięć ósmych)



Odpowiedź :

Odpowiedź:

3(2x-4)-5(4x+7)=6x-12-20x-35=-14x-47

(2x-6)(3x+5)+4x-9=6x^2 +10x-18x-30+4x-9=6x^2 -4x-39

(2a-3)(5-4a)-6a(2a+4)=10a-8a^2 -15+12a-12a^2 -24a=-20a^2 -2a-15

3x-4y+7=3*(-2)-4*(-5)+7=-6+20+7=21

6x-8y+12+x^2=6*(-2)-8*(1 1/2)+12+(-2)^2=-12-12+12+4=-8

12a-16b+8=12*(3/4)-16*(5/8)+8=9-10+8=7

Mam nadzieję, że pomogłam ;)